The role of proprioceptive system in the rehabilitation of patients after Achilles tendon reconstruction - Strojek, Katarzyna; Weber-Rajek, Magdalena; Zukow, Walery; Radzimińska, Agnieszka (Journal of Education, Health and Sport, 2017)
Achilles tendon injury is a major clinical problem because it prevents proper functioning of the patient. The recommended procedure in the event of tendon rupture is surgical treatment - reconstruction of tendon reconstruction. The aim of surgical treatment of Achilles tendon rupture is to bring back its function by restoring the correct length and tension of the tendon and to obtain the highest possible functional state of the patient. The selection of the optimal post-operative rehabilitation programme with a predominance of functional physiotherapy elements is an essential part of the treatment of Achilles tendon rupture. A proper rehabilitation after the surgery enables the patient to achieve better functional results. During the surgery proprioceptors are damaged, that is why the treatment working on three levels of motor control should be introduced as fast as possible, such as kinesthetic or proprioceptive training.